APRESENTAÇÃO DOS CADERNOS DO IL 53 - Rodrigues Boff, Camila; Ferreira Pavani, Cinara; Tomm, Davi Alexandre; Mondadori Simionato, Deborah; Chagas da Costa, Monica; Barros de Freitas, Olívia; Cristine Hoff, Patrícia (Cadernos do IL, 2017)
Apresentação do nº 52 dos Cadernos do IL - Estudos Literários.